Market Valuation and Financial Performance: ESG, Carbon Disclosure, Sales Growth with Firm Size as Moderation - Naurah Aqilah Busnia; Abdul Mukti Soma (ADPEBI Publisher, 2026)
Purpose - Although sustainability and corporate growth have garnered increased attention, their impact to company value and financial success remains equivocal. The purpose of this study is to investigate the impact of Carbon Emission Disclosure (CED), Environmental, Social, and Governance (ESG), and Sales Growth on market valuation and financial performance, and to explore the moderating role of Firm Size in energy companies of five ASEAN countries, for the period 2022–2024. Methodology/approach – The study adopted a quantitative research strategy employing secondary data obtained from annual reports, sustainability reports and the Refinitiv database. Businesses were pre-defined criteria. The Regression Regression Regression Regression Regression Regression Regression Regression Regression Regression Regression Regression Regression. Financial Financial Financial Financial performance. Findings – The results show that CED has no significant effect on market valuation or financial performance. ESG has no material impact on market valuation but positive impact on financial performance. Sales Growth has a positive impact on both variables. Firm Size does not moderate the relationship between CED, ESG, Sales Growth and market valuation. Nevertheless, it diminishes the effect of CED and ESG on financial performance, while the moderating effect of Sales Growth is not evident. Novelty/value – Using firm size as a moderator, this article creates an integrated framework for CED, ESG, and sales growth in the ASEAN energy sector. The findings indicate that sustainability disclosure has less of an impact on firm value and financial performance than growth-related characteristics.